Driving successful internal change A study on how to manage people-issues, key success factors and the role of change agents - Elinor, Zacharias (My University, 2021)
This study seeks to investigate how an internal change is undertaken at a high-tech established company, especially it studies the process of change and the role of change agents, in order to contribute to solutions to overcome the challenges that may arise in change projects. The case study has been undertaken at an international company operating in the telecom industry by comparing two attempts of the same change project. Three sub-questions are studied derived from the main research question: how does a change process look like in a high-tech company. The sub-questions are a) what could be the success factors in a change process, b) how are challenges in relation to human behavior handled in high-tech firms during a change process, and c) what role does a change agent play in a change process. The study is conducted by using an inductive approach. It included a literature study of current theory about change management, interviews with change agents and change recipients at the company as well as through participant observation. Eight interviews were held in a semi-structured manner and the result was analyzed by identifying common themes. Structure and participation were identified as success factors and catalysts for making a positive cumulative process with other important factors to take place. Having supportive processes in place for handling challenges connected to people was seen as important for high-tech companies and to be able to adapt to the specific situation. Furthermore, the result showed that change agents are critical in ensuring the process is implemented and sustained, but it is not enough to secure success.